Genesıs, Ecosystems And Prıncıples - Peñaranda Galvis, Vidal Fernando, Rodríguez Miranda, Juan Pablo, Gómez Aguilar, Dora Luz (International Journal of Advanced Science and Technology, 2020)
The strength of being is in the ability to build new ways of life to live with their peers. Wherever he stops, his spirit must inhabit the whole environment with pleasure, the signs will be the open meeting of temperance that reduces distances. Under each roof, the coexistence will be marked, and there will always be the expectation of the farewell, latent in watching over the wait and march of the happy encounter in the return.